MICROWAVE-ASSISTED SYNTHESIS OF COVALENT ORGANIC POLYMER ADSORBENT FOR EFFICIENT C02 CAPTURE - YAQUB, SANA (2015)
Recent advancement in CO2 capture technology showed a promising trend in the development of covalent organic polymer (COP) adsorbent for CO2 capture. Although the COP adsorbent is very robust with high CO2 uptake, it suffers a major drawback of long synthesis time. Thus, this study investigates the possibility of reducing the synthesis time via the application of microwave reaction system while maintaining the desired characteristics of the covalent organic polymer adsorbent. Here a series of COP-4 adsorbents (COP-4A, B, C, D, and E) are synthesized at various synthesis temperature and synthesis time. Initial findings showed that microwave method has successfully synthesised the COP-4B adsorbent within 4 hours, thus reducing the synthesis time from 12 hours to 4 hours. Greater reduction in synthesis time was observed at elevated synthesis temperatures. The characterisation results of these COP-4 adsorbents showed strong agreement with reported literature.